Experimental and Pathological study of renal toxicity by food salt in broilers - Al-Kaabe, H. T.; Falih, Ena'am B.; Al-Hyali, H. M. (The Iraqi Journal of Veterinary Medicine, 2003)
A Forty-broiler chick one-day-old divided randomly & equally into two groups of twenty each. The First group was give drinking water contain 0.5% food salt. The Second group (control group) receiving normal drinking water. The experimental study from one day for 35 day. Clinically chicks receiving salted water showed server thirst, watery diarrhoea, loss of appetite with loss of body weight. Control group was clinically normal. At the end of the 35-day experimental study birds were sacrificed by severance of the headMacroscopic examination, changes were restricted to the kidneys. They were pale in colour, reduced in size with granules palpated kidney superficial surface. Histopathological examinations of the kidneys there were evidence of glomerular seclerosis in some glomeruli, other appeared atrophied. Also there was evidence of thickened hypertrophic media of renal arteries & arterioles.